Critical control point-based assessment and intervention of ochratoxin A risk in Angelicae Gigantis Radix production - Kim, Juil; An, Tae Jin; Moon, Yuseok (Frontiers in Microbiology, 2022)
Improperly practiced postharvest procedures can pose mycotoxin-related risks during medicinal herb production. As a health food material with pharmacological activities, Angelicae Gigantis Radix (AGR) has been extensively used in oriental medicine or functional foods. Compared with the official protocol, conventional practices were investigated for provisional critical control points (CCPs) in terms of ochratoxin A (OTA) contamination. Conventional practices include field-drying, which was associated with increased fungal exposure. Compared with conventional methods, the washing process in the official protocol was not advantageous for reducing OTA contamination in final products. Instead, drying was examined to assess the fungal growth risk during AGR production. To reduce the energy cost, product overload and shortened drying time could lead to failure in controlling fungal overgrowth and subsequent OTA production. In particular, inner parts of the load contained a higher OTA content than outer parts close to the heat outlet of the dryer. Improper thermal drying of loads allowed the growth of ochratoxigenic species during AGR production. Collectively, non-field-drying and optimally loaded thermal drying are easy preventive actions in key CCPs that need to be well maintained to attenuate any further microbial risk. These assessments provide insights into good practice-based mycotoxin risk management in producing herbal medicinal crops and new cost-efficient appropriate interventions for small-scale farms.